In Vitro Evaluation of a Device to Assess Acetabular Cup Position by Sagittal Plane Radiography - Karlin, W. Michael; Lirtzman, Ross; Kowaleski, Michael P. (Veterinary and Comparative Orthopaedics and Traumatology, 2025)
The purpose of this study was to compare the calculated angle of lateral opening (ALO) and open-face version obtained using an acetabular cup position assessment device (CPAD) to the known ALO and open-face version of an acetabular component. The null hypothesis was that there would be no significant differences between the ALO and open-face versions using the CPAD compared with the known values.Radiographic images simulating a sagittal plane pelvis were obtained with a BFX™ acetabular component containing a CPAD mounted on a plexiglass jig with a dual-plane inclinometer. Images were obtained at an open-face version of 0 degrees with ALO at 30, 40, 45, 50, and 60 degrees, repeated in triplicate, and were randomized. Measurements of the CPAD bars were used to calculate the open-face version, and ALO measurements were compared using a paired t-test with a p-value set at p < 0.05. Agreement was assessed with a Lin's Concordance Correlation Coefficient.The calculated ALO was not significantly different from the known ALO (p = 0.608) and showed near-perfect correlation of the ALO with a Lin's Concordance Correlation Coefficient (Rc value) of 0.994. The calculated open-face version was significantly different from the known version.The results demonstrate that the CPAD is an accurate method to determine ALO in a simulated sagittal plane pelvis radiographic view.
Keywords: total hip arthroplasty; acetabular component; angle of lateral opening; cup position assessment device; version